Assessment of a medical student led sex education curriculum for at risk US 9th graders aged 14–15 years. Issue 1 (2nd January 2020) - Yang, Sophia; Mcquade, Miriam; Lovio, Marissa; Leaf, Marie-Claire; Barron, Kathryn; Brabender, Danielle; Hostetter, Isaure; Lo, Alyssa; Marik-Reis, Olivia; Raman, Kaavya; Roy, Kevin; Patel, Priya A.; et al.
ABSTRACT: Santa Ana, California has the highest teenage birth rate in Orange County, USA, at 28.2 per 1, 000 women aged 15–19 as compared to 12.0 per 1000 women of similar age elsewhere in the county. In the light of this disparity, University of California Irvine medical students surveyed a convenience sample of 9th grade students (aged 14–15 years) in Santa Ana to assess the efficacy of a medical student-led sex education programme. Nine 50-minute sex education lessons were conducted over a 2-week period, with pre- and post-tests to evaluate knowledge retention. A total of 301 pre-tests and 295 post-tests were collected. Of 27 multiple choice questions, the mean number of correct questions on the pre-test was 11.3 (± 4.2) compared to 14.1 (± 5.0) questions on the post-test. There was significant improvement in scores following the implementation of the curriculum (p < 0.001). Overall, findings demonstrate that medical students can effectively teach a sex education curriculum. The study serves as a potential model for sex education in geographic areas that exhibit disparities in teenage birth rates.